HASIL, KOMPONEN HASIL, HETEROSIS BAKU DAN PRODUKTIVITAS PER HARI SEMBILAN GENOTIPE PADI HIBRIDA JAPONICA DI LAHAN SAWAH BERPENGAIRAN TEKNIS - Bambang Sutaryo (Universitas Muhammadiyah Purwokerto, 2013)
This research is to study about the yield, yield components, standard heterosis and productivity per day for nine rice genotypes on low land rice irrigation such as Biojap-1, Biojap- 2, Biojap-3, Biojap-4, Biojap-5, Biojap-6, WM4, DG1-SHS, and Taiken and a check variety namely: Ciherang was evaluated for their agronomic characters at Tamanan, Banguntapan, Bantul from November 2012 to March 2013. Experiment design was randomized complete block design with four replications. Seedling with 17 days age was planted with one seedling per hill, in plot size of 4 x 5 m2. Fertilization at nursery was applied three times, and four times during vegetative and 5% generative stages. Data indicated that Biojap-2, Biojap-3 and Biojap-5 yielded 8.6; 8.4; and 8.3 t/ha significantly over the best check variety DG1-SHS (7.8 t/ha). Those hybrids were also earlier, and slightly shorter than that of DG1-SHS. Productivity per day for Biojap-2, Biojap-3 and Biojap-5 were 93.07; 91.11 and 88.58 kg/ha, with percentage over DG1- SHS were 15.03; 12.61; and 9.48 %, respectively. Filled grain per panicle of Biojap-2, Biojap-3 and Biojap-5 were 234.2; 221.5; and 218.6 seeds, respewctively, and significantly higher than that of DG1-SHS (188.4 grain). Those hybrids also showed significantly in term of longer panicle and weighter for 1000-grain weight. Standard heterosis variation for yield, maturity, plant height, filled grain per panicle, panicle lenght and 1000-grain weight for Biojap-2, Biojap-3 and Biojap-5 were (6.41-10.26%), -4,11 to -5,24%), (-3,42 to -6,37%), (16,03-24,31%), (4,37-8,73%) and (5,43-7,75%), respectively. Key words : yield, yield component, standard heterosis, nine japonica rice genotypes, low land rice irrigation.